Experimental queen removal stimulates caste flexibility of females in Neotropical social wasps (Vespidae Polistinae Epiponini) - Chavarría-Pizarro, Laura; Chavarría-Pizarro, Tania; Noll, Fernando B. [UNESP] (Taylor & Francis, 2024)
Caste plasticity is an essential trait in social insects, and it facilitates the allocation of individuals in different tasks according to population demands in the colony (e.g. workers can become queens upon loss or death of their “original queen”). The process of caste determination can take place in immature stages (preimaginal) or through adult stages (imaginal). Neotropical social wasp tribe Epiponini has both types of caste determination process and is thus a fascinating group to study caste plasticity. We performed queen removal tests in five Epiponini species with preimaginal and imaginal caste determination to better understand caste plasticity and queen selection processes. Queen absence stimulates the establishment of new reproductive females in Chartergellus and Metapolybia (imaginal), while females in Protopolybia (preimaginal) attempt to lay eggs even in the presence of their “original queen”. Contrary to what has been hypothesized, we found that age is not a predictive factor in the female’s potential to become a queen. Caste flexibility seems to be a crucial trait which aids Epiponini tropical colonies to survive, as it allows the colony to replace lost workers and queens promptly until a new generation of wasps can emerge.
Keywords: caste; determination; plasticity; queen lost; social wasps